ANALISIS PENGEMBANGAN PERIKANAN PURSE SEINE KABUPATEN ACEH BESAR - Aulia Putra; Tri Wiji Nurani; Prihatin Ika Wahyuningrum (Buletin PSP, 2012)
Purse seine is one the productive fishing gear for fishing pelagic fishes.  Fishing capacity is one the important issue in sustainable fisheries. This study aimed to measure fishing capacity of purse seine in Aceh Besar district, estimated the maximum economic yield (MEY) the targeted pelagic fishes, and formulate management strategies purse seine in the district of Aceh Besar.  Fishing capacity was analyzed using the data envelopment analysis (DEA) method based on fishing capacity efficiency of monthly total catch as single output, from September 2009 to August 2010.  Fishing vessel was used as decision making unit (DMU).  Fixed input consists gross tonnage (GT), engine horse power (HP) and length of webb. Variable input consists number of crew, lamp power (watt), hold capacity (ton), and number of trip. The result showed that fishing capasity, 17 vessels reached optimum (CU=1), and fishing capacity of purse seine was 257 ton/year/unit. Thus bioeconomic analysis of pelagic fishes showed that MEY reached at 3,753.37 ton/year and optimum effort at 8,623  trip/year with total cost Rp 34,992,314,500 year and total revenue Rp 51,643,083,629. Management strategy for purse seine fishery in Aceh Besar district is the development of technology, human resource  development and the role of institutions such as institutions laot commander.   Key words: Aceh Besar district, fisheries development, management strategies, maximum economic yield (MEY), purse seine